Finite Element Analysis and Optimization of Medium Bus Frame Structure - Kurniadi, Ninda; Priyanto, Kaleb; Gojandra, Farda Pega Libra (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2025)
Bus is a very important transportation for all people in the world. The majority of a bus that operates still uses non-renewable fuel. The conventional bus produces exhaust emissions that can damage the environment. Current research is about changing the conventional internal combustion engine bus into an electric bus, therefore it is necessary to test the strength of the frame structure to determine its strength after changing with the electric system. The objective of this current study is to analyze the bending strength and optimization of a medium electric bus frame structure using the Finite Element Method in static conditions. Optimization will be conducted after obtaining results of bending analysis to determine the minimum weight of the bus frame structure without violating bending strength. The results of the bending analysis are stress and displacement which will be used as a constraint in the optimization process. The optimization that will be used is size optimization. The design variable is the thickness of each bus frame structure. Results show that the weight of the structure is reduced by 12% without compromising on strength and safety requirements.